Characterisation of quinoa (Chenopodium quinoa Willd.) accessions for the saponin content in Mediterranean environment - De Santis, Giuditta; Maddaluno, Carmen; D’Ambrosio, Tiziana; Rascio, Agata; Rinaldi, Michele; Troisi, Jacopo (Italian Journal of Agronomy, 2016)
Seeds of the Andean seed crop quinoa (Chenopodium quinoa Willd.) usually contain saponins in the seed coat. Saponins give a bitter taste sensation and are a serious antinutritional factor, therefore selection of sweet genotypes with a very low saponin content in the seeds is a main breeding goal. The objective of this work was to identify, within germplasm lines of quinoa, previously selected for production and quality traits, superior genotypes low in saponins. For this purpose the total saponin content was determined in seeds of eight lines of quinoa and one variety (cv. Regalona Baer) as a control, previously evaluated over a 2-year period in a Southern Italy environment. Significant variation for the saponin content was observed among the evaluated genotypes. The total saponin content ranged from 0.10 to 1.80%, with the Q12 genotype showing the lowest value, suggesting the possibility of selecting genotypes sweet to be used in subsequent genetic improvement programs. Based on these results, in fact, it was possible to identify, among the accessions previously selected, particularly suitable for growing in Mediterranean area, some genotypes with high yields of seed (2.5 tha–1, on average), high protein (17%, on average) and fibres (13%, on average) and low content in saponins (0.57%, on average).